The language teaching matrix - Richards, Jack C. (Cambridge University Press, 1990)
Richards explains how effective language teaching involves a network of interactions between curriculum, methodology, teachers, learners, instructional materials. Each chapter discusses and examines the theoretical and practical dimensions of a central issue in language teaching. Topics covered include the nature of effective teaching, self-monitoring in teacher development, language and content, and teaching listening, speaking, reading and writing. Richards presents key issues in an accessible and highly readable style, and shows how teachers and teachers-in-training can be involved in the investigation of classroom teaching and learning. The emphasis is not on prescriptions but rather on developing effective teaching through understanding the various factors that interact in second language learning and in the second language classroom